2008
DOI: 10.1215/15228517-2007-035
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of human cytomegalovirus in tumors and peripheral blood of patients diagnosed with glioblastoma

Abstract: Human cytomegalovirus (HCMV) has been described to be associated with several human malignancies, though the frequency of detection remains controversial. It is unclear whether HCMV plays an active role in malignant tumor progression or becomes reactivated under pathologic conditions that result in chronic inflammation or immunosuppression. In this study, we report on the investigation of detecting HCMV in the tumors and peripheral blood of patients with newly diagnosed glioblastoma multiforme (GBM). Using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
287
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(311 citation statements)
references
References 44 publications
18
287
1
2
Order By: Relevance
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 91%
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 91%
“…42: 3256-3266 Immunity to infection 3257 lifelong latent state, occasionally undergoing reactivation, but may have a pathogenic role in immunodeficient and immunosuppressed patients [1][2][3]. Moreover, HCMV has been associated with atherosclerosis, lymphoproliferative disorders, and glioblastoma, as well as with an accelerated immunosenescence and a shorter lifespan [4][5][6][7]. Vertical transmission of HCMV during pregnancy is considered the most common cause of congenital infection worldwide, affecting ∼0.2-2% of infants and potentially causing fetal lesions [8][9][10].…”
mentioning
confidence: 99%
“…However, more studies investigating the importance of HCMV in brain tumours have emerged. Mitchell et al (2008) detected HCMV in the tumours and peripheral blood of patients diagnosed with GBM and normal controls using IMH, ISH and PCR of viral DNA. They showed that a high percentage (> 90%) of GBM tumours were associated with HCMV nucleic acids and proteins.…”
mentioning
confidence: 99%